Effects of sputtering pressure on the growth of AlGaN thin films using Co-sputtering technique - Othman, Nur Afiqah; Nayan, Nafarizal; Kamarulzaki, Mohd; Azman, Zulkifli; Bakar, Shuhaimi Abu; Mamat, Mohd; Mohd Yusop, Mohd Zamri; Ahmade, Mohd Yazid (Indochina Applied Sciences, 2023)
Aluminium gallium nitride (AlGaN) thin films provide promise for a variety of electronic devices due to their wide energy bandgap, which ranges from 3.11 – 6.40 eV. Here, a co-sputtering approach utilising the RF and HiPIMS power supply of magnetron sputtering is used to deposit the AlGaN thin films. To examine their impact on the structural characteristics and morphology of the thin films, the AlGaN thin films were deposited under various sputtering pressures using the co-sputtering technique. Following that, the films were examined using X-ray diffraction (XRD), atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM), and surface profiling to determine their characteristics. XRD shows the polycrystalline AlGaN with (100), (101), (102), and (110) plane for the AlGaN deposited at a sputtering pressure of 3 mTorr and 5 mTorr with FWHM 0.622° and 0.732°, respectively. The increasing the sputtering pressure to 5 mTorr is found to improve the crystallinity as well as the thickness of the AlGaN thin films from 234.27 – 1479.37 nm. AFM examination of the AlGaN film revealed a trend of increasing roughness and grain size together up to 3.25 nm and 47.22 nm respectively, with rising sputtering pressure from 1 – 7 mTorr. The co-sputtering of AlGaN can be successfully demonstrated in this study, and it is also shown that the sputtering pressure has a substantial impact on the development of AlGaN thin films produced using this technology.